RUNX1 promotes proliferation of cervical cancer through TGFB2-MAPK pathway - Yongqin Jia; Neng Yang; Shuai Tang; Li Deng; Yanzhou Wang; Xiongwei Cai (Scientific Reports)
Abstract As cervical cancer (CC) caused more than 300,000 deaths in the world, it is urgent to identify therapeutic targets to improve survival. Though RUNX1 is overexpressed in CC, its specific role and underlying molecular mechanisms remain incompletely understood. Here we presented that RUNX1 was upregulated in CC and associated with poor prognosis. Functional studies demonstrated that RUNX1 acts as an oncogene in CC, with overexpression accelerating cell cycle progression and promoting cell proliferation. Mechanistically, RUNX1 regulates the MAPK pathway by modulating TGFB2 expression, while TGFB2 inhibition impaired MAPK pathway activation and the proliferation driven by RUNX1 overexpression. Comprehensive analyses also suggested that RUNX1 may modulate the immune microenvironment in CC through TGFB2. These findings indicate that RUNX1 promotes CC progression by activating the MAPK pathway through upregulation of TGFB2. Our study provides new insights into the role of RUNX1 in CC proliferation and suggests RUNX1 as a potential therapeutic target in CC.